Identification of Cyclamate Among Contemporary Drinks in Urban Area of Mamuju Regency - Fahrul Islam; Haeranah Ahmad; Sitti Saddania (Indonesian Journal of Global Health Research, 2022)
There are still many problems in the use of artificial sweeteners in Indonesia. Artificial sweeteners are still often used above the allowable threshold. Cyclamate is one of the sweeteners that is often used in Indonesia. Cyclamate has no caloric value and is difficult to absorb by the gastrointestinal tract. However, a number of variables hydrolyzed by bacteria in the intestinal tract can form cyclohexilamine which is a potential carcinogen. Two scientific studies linked cyclamate to the production of rat bladder cancer tumors which led to cyclamate being banned from use in many countries. This study was to identify cyclamate content among contemporary drinks in Urban Area of Mamuju Regency. This research was conducted in June – August 2022. The sample of this study is a contemporary drink circulating in the Urban Area of Mamuju Regency as many as 30 brands. The research method uses observational methods with a descriptive approach. Cyclamate content is measured using gravimetric methods. based on SNI 01-2893-1992 concerning How to Test Artificial Sweeteners. Data collection is carried out by taking samples of contemporary drinks and then checking the cyclamate content in the laboratory. The samples taken are drinks with the best-selling flavor variants in each brand. The measurement result is compared with the threshold standard. It is said to exceed the threshold if the weighing results are above 3 mg / L. This study was analyzed using descriptive analysis. All samples examined contained cyclamate with the lowest content of 1.19 gr/L and the highest at 237.9 gr/L and 24 brands of contemporary drinks containing cyclamate above 3gr/L. Conclusions: 80% of contemporary drinks circulating in Urban Area of Mamuju Regency contained cyclamate exceeding the threshold.